A nanocrystalline iron core and its preparation method and pulse transformer

By applying stress and controlling the heat treatment process during the preparation of nanocrystalline iron core, the problems of the flux variation and magnetic loss of the existing iron core are solved, and efficient pulse flux variation and low loss core performance are achieved.

CN119764006APending Publication Date: 2025-04-04CHINA IRON & STEEL RESEARCH INSTITUTE GROUP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411802582.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing iron core has a low flux change ΔB in single-stage pulse mode and a large hysteresis loss, making it difficult to meet the needs of high-power signal-type pulse transformers.

Method used

By applying stress to the nanocrystalline strip and winding it into an annular iron core, combined with the process of rapidly increasing the heat to above the crystallization temperature, rapid cooling and applying a transverse magnetic field, the microstructure and magnetic domain structure of the nanocrystalline strip are regulated, thereby improving the soft magnetic characteristics of the iron core.

Benefits of technology

The high single-stage pulse flux variation of the iron core is realized ΔB≥1.1T and low magnetic loss Ps <100W/Kg. It is suitable for high-power signal pulse transformers, providing larger output power and lower losses.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764006A_ABST
    Figure CN119764006A_ABST
Patent Text Reader

Abstract

The present invention relates to a nanocrystalline iron core and a preparation method thereof and a pulse transformer, and belongs to the technical field of nanocrystalline soft magnetic core processing. The preparation method of the nanocrystalline iron core is to apply stress to a nanocrystalline strip and wind it into an annular iron core, and the magnetostriction coefficient λs of the nanocrystalline strip is ≠0; then the annular iron core is heated to above the crystallization temperature and kept warm, and then quickly cooled to below the crystallization temperature; after it is below the crystallization temperature, a transverse magnetic field is applied and kept warm, and then cooling is continued after the end of the heat preservation; the cooled annular iron core is placed in an iron core protection box, and then filled with epoxy resin glue and cured to obtain a nanocrystalline iron core. The process of quickly heating to above the crystallization temperature, keeping warm, and rapidly cooling is adopted, and the microstructure and magnetic domain structure of the nanocrystalline strip are regulated by superimposing external stress, the soft magnetic properties of the iron core are improved, and an iron core with a higher unipolar pulse magnetic flux change and lower iron loss is obtained, providing a pulse transformer with a larger output power and lower loss.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nanocrystalline soft magnetic core processing, in particular to a nanocrystalline iron core and a preparation method thereof and a pulse transformer. Background Art

[0002] As high-power power supply technology and electronic power technology develop towards miniaturization and high efficiency, higher and higher requirements are placed on the performance of internal components of electronic systems. Among them, pulse transformers can realize power transmission, voltage conversion and insulation isolation functions. They are the core components for pulse signal transmission in electronic power systems and are widely used in radar, laser, accelerator, power and switching power supplies. The basic principle of pulse transformers is similar to that of ordinary power transformers, but they also have their own unique waveform characteristics and functions. They are divided into unipolar and bipolar types. The former only works in a unidirectional pulse state and does not require a DC bias magnetic field to work. It can simplify the circuit while achieving the same performance and has great application prospects.

[0003] The iron core is the heart of the pulse transformer. The volume, working efficiency and quality of the transformer are all determined by the comprehensive soft magnetic properties of the iron core. In the unipolar pulse mode, the magnetic induction increment ΔB of the iron core magnetic flux density changes from the maximum value Bm to the residual magnetic flux density Br, that is, ΔB = Bm-Br, is the main performance to be paid attention to in the development of new iron core materials suitable for high-power signal pulse transformers.

[0004] According to the random anisotropy model, the magnetic domain structure inside the nanocrystalline ribbon presents a spot domain structure, and the magnetization process is dominated by irreversible magnetic moment rotation, which will cause the Br of the material to be very large, ultimately affecting the ΔB of the iron core under a unipolar pulse and causing hysteresis losses.

[0005] In order to increase ΔB and reduce hysteresis loss, the existing method for preparing the iron core is to improve the performance through transverse magnetic annealing, but the effect is relatively limited and due to the uneven release of stress, the introduction of stress will lead to problems such as cracking. Summary of the invention

[0006] In view of the above analysis, the present invention aims to provide a nanocrystalline iron core and a preparation method thereof and a pulse transformer to solve the problem that the single-stage pulse magnetic flux change ΔB of the existing iron core is low and the hysteresis loss is large.

[0007] In one aspect, the present invention provides a method for preparing a nanocrystalline iron core, comprising the following steps:

[0008] S1: The nanocrystalline ribbon is wound into a ring-shaped core while applying stress, and the magnetostriction coefficient λs of the nanocrystalline ribbon is ≠0;

[0009] S2: heating the annular core to a temperature above the crystallization temperature and then rapidly cooling the core to a temperature below the crystallization temperature;

[0010] S3: applying a transverse magnetic field and keeping the temperature below the crystallization temperature, and continuing cooling after the temperature is kept;

[0011] S4: Place the cooled annular core into a core protection box, fill it with epoxy resin glue and solidify it to obtain a nanocrystalline core.

[0012] Furthermore, the stress application direction is associated with the positive and negative values ​​of λs of the nanocrystalline ribbon. When λs>0, the applied stress is a compressive stress parallel to the extension direction of the ribbon; when λs<0, the applied stress is a tensile stress parallel to the extension direction of the ribbon.

[0013] Furthermore, the magnitude of the stress is 10-60 MPa.

[0014] Furthermore, in step S2, the heating rate is 30-50°C / min, and the holding temperature is 50-150°C above the crystallization temperature.

[0015] Furthermore, in step S2, the insulation time is 30 min-120 min.

[0016] Furthermore, in step S3, the insulation temperature for applying the transverse magnetic field is 250-350° C., and the insulation time is 60 min-150 min.

[0017] Furthermore, the composition of the nanocrystalline ribbon is Fe-Co, Fe-Ni, Fe-Hf-B, Fe-Al, Fe-Si-Al, Fe-Pt or FeCuNbSiB.

[0018] Furthermore, when the saturation magnetic flux change Bs of the nanocrystalline core is ≥1.2T, the single-stage pulse magnetic flux change ΔB of the nanocrystalline core is ≥1.1T; at 100kHz and 0.3T, the nanocrystalline core loss Ps is <100W / Kg.

[0019] In another aspect, the present invention provides a nanocrystalline iron core obtained by the preparation method provided by the present invention, which can be used for preparing or applying in a pulse transformer.

[0020] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0021] 1. The present invention adopts a process of rapidly heating to a temperature above the crystallization temperature, keeping the temperature, and rapidly cooling, and superimposes external stress to regulate the microstructure and magnetic domain structure of the nanocrystalline strip, thereby improving the soft magnetic properties of the iron core, obtaining an iron core with a higher unipolar pulse flux change and lower iron loss, and providing a pulse transformer with a larger output power and lower loss;

[0022] 2. The preparation method of the pulse transformer core of the present invention superimposes external stress when winding the strip, which is equivalent to superimposing stress anisotropy, thereby regulating the magnetic domain structure of the nanocrystalline strip to make it close to the 180-degree domain structure, thereby improving the soft magnetic properties of the core, and obtaining a core with a higher single-pole pulse magnetic flux change and lower iron loss, providing a pulse transformer with a larger output power and lower loss; the nanocrystalline core of the present invention, the single-pole pulse magnetic flux change ΔB ≥ 1T; the average pulse magnetic permeability μp at 100kHz> 10000; at 100kHz, 0.3T, the core loss Ps < 100W / Kg.

[0023] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The drawings are only for the purpose of illustrating specific embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.

[0025] Figure 1 This is the cross-sectional structure diagram of the nanocrystalline core of the pulse transformer;

[0026] Figure 2 Schematic diagram of the direction of magnetic field application;

[0027] Figure 3 Schematic diagram of stress application direction and magnetic domain direction;

[0028] Figure 4 This is an atomic force microscope image of the nanocrystalline ribbon of Example 1;

[0029] Figure 5 This is a magnetic force microscope image of the nanocrystalline ribbon of Example 1;

[0030] Reference numerals:

[0031] 1. Core protection box; 2. Epoxy resin glue; 3. Nanocrystalline strip. DETAILED DESCRIPTION

[0032] The preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of the present invention and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.

[0033] As high-power power supply technology and electronic power technology develop towards miniaturization and high efficiency, higher and higher requirements are placed on the performance of internal components of electronic systems. Pulse transformers can realize power transmission, voltage conversion and insulation isolation functions. They are the core components for pulse signal transmission in electronic power systems and are widely used in radar, laser, accelerator, power and switching power supplies.

[0034] The iron core is one of the core components of the pulse transformer. The volume, working efficiency and quality of the transformer are all determined by the comprehensive soft magnetic properties of the iron core. According to the random anisotropy model, the magnetic domain structure inside the nanocrystalline ribbon presents a spot domain structure, and the magnetization process is mainly based on irreversible magnetic moment rotation, which will cause the Br of the material to be very large, ultimately affecting the ΔB of the iron core under a unipolar pulse, resulting in hysteresis loss.

[0035] In order to increase ΔB and reduce hysteresis loss, the existing method for preparing the iron core is to improve the performance through transverse magnetic annealing, but the effect is relatively limited and due to the uneven release of stress, the introduction of stress will lead to problems such as cracking.

[0036] The present invention provides a method for preparing a nanocrystalline iron core, comprising the following steps:

[0037] S1: The nanocrystalline ribbon is wound into a ring-shaped core while applying stress, and the magnetostriction coefficient λs of the nanocrystalline ribbon is ≠0;

[0038] S2: heating the annular core to a temperature above the crystallization temperature and then rapidly cooling the core to a temperature below the crystallization temperature;

[0039] S3: applying a transverse magnetic field and keeping the temperature below the crystallization temperature, and continuing cooling after the temperature is kept;

[0040] S4: Place the cooled annular core into a core protection box, fill it with epoxy resin glue and solidify it to obtain a nanocrystalline core.

[0041] Compared with the prior art, the preparation method of the pulse transformer core of the present invention superimposes external stress when winding the strip, which is equivalent to superimposing stress anisotropy, thereby regulating the magnetic domain structure of the nanocrystalline strip to make it close to a 180-degree magnetic domain structure, and then optimizing the heat treatment process to improve the soft magnetic properties of the core, thereby obtaining a core with a higher unipolar pulse magnetic flux change and lower iron loss, providing a larger output power and lower loss for the pulse transformer.

[0042] Specifically, the stress application direction is associated with the positive and negative of λs of the nanocrystalline strip. When λs>0, the applied stress is a compressive stress parallel to the extension direction of the strip; when λs<0, the applied stress is a tensile stress parallel to the extension direction of the strip.

[0043] It should be noted that applying stress while winding the strip can, firstly, apply stress in the initial stage to help release the stress in the nanocrystalline strip, reduce the risk of abnormal grain growth and cracking in subsequent heat treatment, increase ΔB, and reduce hysteresis loss; secondly, the strip winding and stress treatment can be carried out simultaneously to simplify the process flow and control the cost.

[0044] Specifically, the magnitude of the stress is 10-60 MPa.

[0045] Preferably, the magnitude of the stress is 40-50 MPa.

[0046] It should be noted that the stress in the nanocrystalline strip can be released after the stress is applied, and the stress is controlled within 10-60MPa, which can reduce the hysteresis loss well on the one hand, and will not exceed the yield strength of the nanocrystalline strip on the other hand, ensuring its safety. When the stress exceeds 60MPa, the risk of the strip breaking is greatly increased, and the flux change and magnetic permeability are too low, affecting the use of the core; when the stress is lower than 10MPa, the effect on the strip microstructure and magnetic domain structure is not obvious, and the improvement of ΔB and the reduction of hysteresis loss are limited.

[0047] Specifically, in step S2, the heating rate is 30-50°C / min, and the holding temperature is 50-150°C above the crystallization temperature.

[0048] Specifically, in step S2, the insulation time is 30 min-120 min.

[0049] Specifically, in step S2, the rapid cooling method is a water cooling method.

[0050] It should be noted that in the present invention, the nanocrystalline strip formed by winding needs to be heat treated, and the process is heating, heat preservation and rapid cooling. During the heating process, the heating rate needs to be controlled. If the heating is too fast, that is, the heating rate is greater than 50°C / min, it may cause the grains in the nanocrystalline strip to grow or unevenly crystallize; and if the heating is too slow, that is, the heating rate is less than 30°C / min, it may cause incomplete crystallization of the ring core or strip, affecting the nanocrystalline core.

[0051] The holding temperature of the present invention is 50-150°C above the crystallization temperature and is kept for 30min-120min. The holding temperature can promote the refinement of the material grains, while too high or too low a temperature may cause grain growth or incomplete crystallization. Similarly, too long a holding time may cause grain growth, while too short a holding time may not complete the crystallization process. Generally, the crystallization temperature is related to the nanocrystalline ribbon and can only be determined after the composition of the nanocrystalline ribbon is determined.

[0052] The present invention adopts a rapid cooling method in the cooling stage, and rapidly cools to below the crystallization temperature. After the crystallization is completed, a fine grain structure can be retained, thereby ensuring the ΔB of the nanocrystalline iron core and reducing the hysteresis loss.

[0053] Specifically, in step S3, the insulation temperature for applying the transverse magnetic field is 250-350° C., and the insulation time is 60 min-150 min.

[0054] Specifically, the direction of the applied transverse magnetic field is the axial direction of the annular iron core, and the magnetic field strength of the applied field is 600-1200 Gs.

[0055] It should be noted that when the temperature of the transverse field heat treatment is too low, the magnetic domain arrangement or grain orientation cannot be fully activated, which in turn affects the magnetic properties of the final iron core; when the holding temperature is too high, it may cause grain growth or induce phase change of the material, affecting its ultrafine grain structure and thus affecting the magnetic properties. The holding time needs to be controlled at 60min-150min. As the holding time increases, the grains gradually grow, affecting the ultrafine grain structure and magnetic properties of the iron core; if the holding time is short, the time is too short, and the desired grain orientation or magnetic improvement effect may not be achieved. When applying a transverse magnetic field, the magnetic field strength needs to be controlled at 600-1200Gs, which can effectively adjust the magnetic domain structure and grain orientation of the material.

[0056] Preferably, the magnetic field strength of the applied field is 800-1200 Gs.

[0057] Preferably, the magnetic field strength of the applied field is 1000-1200 Gs.

[0058] Specifically, the composition of the nanocrystalline ribbon is Fe-Co, Fe-Ni, Fe-Hf-B, Fe-Al, Fe-Si-Al, Fe-Pt or FeCuNbSiB.

[0059] It should be noted that nanocrystalline ribbons with a certain magnetostriction coefficient have significant advantages in stress treatment. Through reasonable stress-magnetic field joint regulation, nanocrystalline ribbons can achieve optimal regulation of magnetic domains, thereby improving the performance of materials in practical applications. The composition of the nanocrystalline ribbon used in the present invention has an Fe content of 20-80%.

[0060] Specifically, when the saturation magnetic flux change Bs of the nanocrystalline core is ≥1.2T, the single-stage pulse magnetic flux change ΔB of the nanocrystalline core is ≥1.1T; at 100kHz and 0.3T, the nanocrystalline core loss Ps is <100W / Kg.

[0061] It should be noted that the present invention, under the application of stress, combined with a heat treatment process and the application of a transverse magnetic field, and under the coordination of corresponding parameters, obtains an iron core with a high single-stage pulse flux change and low iron loss. When the saturation flux change Bs ≥ 1.2T, the single-stage pulse flux change ΔB of the nanocrystalline iron core is ≥ 1.1T; at 100kHz, 0.3T, the nanocrystalline iron core loss Ps < 100W / Kg. This performance meets the application requirements of the pulse transformer iron core, providing a pulse transformer with a larger output power and lower loss.

[0062] The present invention provides a pulse transformer, comprising the nanocrystalline iron core provided by the present invention.

[0063] In order to more clearly describe the present invention, it is further illustrated by the following examples and comparative examples.

[0064] Example 1

[0065] The preparation of nanocrystalline iron core includes the following steps:

[0066] S1: 25mm wide Fe 87 Hf 5 B 8 (λs<0) The nanocrystalline strip is fixed on a winding device, and a tensile stress of 60MPa is applied to the strip by controlling the winding tension of the device. At the same time, the strip is wound into a ring-shaped iron core, and the specifications of the ring-shaped iron core are 76mm inner diameter, 101mm outer diameter, and 25mm height;

[0067] S2: placing the wound annular core into a heat treatment furnace, introducing high-purity argon gas into the heat treatment furnace, heating the annular core to 560°C (crystallization temperature is 510°C) at a heating rate of 50°C / min, and keeping the temperature for 60 minutes to perform ultra-microcrystallization treatment;

[0068] S3: Cooling the ultra-microcrystalline iron core to 300°C in the furnace, keeping the temperature for 30 minutes, applying a transverse magnetic field of 1000Gs, and then cooling it to room temperature in the furnace;

[0069] S4: Place the cooled iron core into a DMC protective box, inject epoxy resin glue, and cure at room temperature for 24 hours to obtain a nanocrystalline iron core for a pulse transformer (refer to Figure 1-3 ).

[0070] Example 2

[0071] The preparation process of Example 2 is substantially the same as that of Example 1, except that in Example 2, the sample is cooled to 300° C. and kept at this temperature for 30 minutes while applying a transverse magnetic field of 800 Gs, and then cooled to room temperature in the furnace.

[0072] Example 3

[0073] The preparation process of Example 3 is substantially the same as that of Example 1, except that in Example 3, the sample is cooled to 300° C., kept at this temperature for 60 minutes, a transverse magnetic field of 1000 Gs is applied at the same time, and then cooled to room temperature in the furnace.

[0074] Example 4

[0075] The preparation process of Example 4 is substantially the same as that of Example 1, except that in Example 4, the sample is cooled to 250° C., kept warm for 30 minutes, a transverse magnetic field of 1000 Gs is applied, and then the sample is cooled to room temperature in the furnace.

[0076] Example 5

[0077] The preparation process of Example 5 is substantially the same as that of Example 1, except that in Example 5, a tensile stress of 40 MPa is applied.

[0078] Example 6

[0079] The preparation process of Example 6 is substantially the same as that of Example 1, except that a tensile stress of 10 MPa is applied in Example 6.

[0080] Example 7

[0081] The preparation process of Example 7 is substantially the same as that of Example 1, except that Fe 74 Cu 1 Nb 3 Si 15 B 7 (λ>0), a compressive stress of 60MPa is applied, and the holding temperature in step S2 is 620℃ (its crystallization temperature is 530℃). (Refer to Figure 3 )

[0082] Comparative Example 1

[0083] The preparation process of Comparative Example 1 is substantially the same as that of Example 1, except that in Comparative Example 1, the sample is cooled to 300° C., kept at this temperature for 30 minutes, no magnetic field is applied, and then cooled to room temperature in the furnace.

[0084] Comparative Example 2

[0085] The preparation process of Comparative Example 2 is substantially the same as that of Example 1, except that the applied stress in Comparative Example 2 is 0 MPa.

[0086] Comparative Example 3

[0087] The preparation process of Comparative Example 3 is substantially the same as that of Example 1, except that the stress applied in Comparative Example 3 is 70 MPa.

[0088] Comparative Example 4

[0089] The preparation process of Comparative Example 4 is substantially the same as that of Example 1, except that the insulation temperature in step S2 of Comparative Example 4 is 680°C.

[0090] Comparative Example 5

[0091] The preparation process of Comparative Example 5 is substantially the same as that of Example 1, except that the magnetic field strength in Comparative Example 5 is 1500 Gs.

[0092] Performance Testing

[0093] The above embodiments and comparative examples were tested for performance, and the core was wound with 5 turns on the primary side and 35 turns on the secondary side using a MATS-2010SD soft magnetic DC magnetic measuring instrument, and the DC magnetic properties of the core were tested at room temperature. The test results are shown in Table 1.

[0094] Table 1 Performance test results

[0095]

[0096] Combining Examples 1-7 and Comparative Examples 1-5 and referring to Table 1, it can be seen that by adopting the preparation method of the embodiment of the present invention, under the application of stress, combined with a heat treatment process and the application of a transverse magnetic field, and matching the corresponding parameters, an iron core with a high single-stage pulse flux change and low iron loss is obtained. When the saturation flux change Bs≥1.2T of the nanocrystalline iron core, the single-stage pulse flux change ΔB of the nanocrystalline iron core is ≥1.1T; the average pulse permeability μp at 100kHz is greater than 10000; at 100kHz, 0.3T, the nanocrystalline iron core loss Ps<100W / Kg. This performance meets the application requirements of the pulse transformer core and provides a larger output power and lower loss for the pulse transformer.

[0097] Reference Figure 4 After the ultra-microcrystallization treatment at 50 degrees Celsius above the crystallization temperature for 60 minutes, the nanocrystalline ribbon has a smooth surface and small grains. Figure 5 The strip of the nanocrystalline iron core treated in Example 1 is close to a 180-degree stripe domain structure, which can improve the soft magnetic properties of the iron core, obtain an iron core with a higher single-pole pulse flux change and lower iron loss, and provide a larger output power and lower loss for the pulse transformer.

[0098] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A method for preparing a nanocrystalline iron core, characterized in that: The following steps are involved: S1: The nanocrystalline ribbon is wound into a ring-shaped core while applying stress, and the magnetostriction coefficient λs of the nanocrystalline ribbon is ≠0; S2: heating the annular core to a temperature above the crystallization temperature and then rapidly cooling the core to a temperature below the crystallization temperature; S3: applying a transverse magnetic field and keeping the temperature below the crystallization temperature, and continuing cooling after the temperature is kept; S4: Place the cooled annular core into a core protection box, fill it with epoxy resin glue and solidify it to obtain a nanocrystalline core.

2. The method for preparing the nanocrystalline iron core according to claim 1, characterized in that: The stress application direction is associated with the positive and negative values ​​of λs of the nanocrystalline ribbon. When λs>0, the applied stress is a compressive stress parallel to the extension direction of the ribbon. When λs<0, the applied stress is a tensile stress parallel to the elongation direction of the strip.

3. The method for preparing the nanocrystalline iron core according to claim 2, characterized in that: The magnitude of the stress is 10-60 MPa.

4. The method for preparing the nanocrystalline iron core according to claim 1, characterized in that: In step S2, the heating rate is 30-50°C / min, and the holding temperature is 50-150°C above the crystallization temperature.

5. The method for preparing the nanocrystalline iron core according to claim 1, characterized in that: In step S2, the insulation time is 30 min-120 min.

6. The method for preparing the nanocrystalline iron core according to claim 1, characterized in that: In step S3, the insulation temperature for applying the transverse magnetic field is 250-350° C., and the insulation time is 60 min-150 min.

7. The method for preparing the nanocrystalline iron core according to claim 1, characterized in that: The composition of the nanocrystalline ribbon is Fe-Co, Fe-Ni, Fe-Hf-B, Fe-Al, Fe-Si-Al, Fe-Pt or FeCuNbSiB.

8. The method for preparing the nanocrystalline iron core according to claim 1, characterized in that: When the saturation magnetic flux change Bs of the nanocrystalline core is ≥1.2T, the single-stage pulse magnetic flux change ΔB of the nanocrystalline core is ≥1.1T; at 100kHz and 0.3T, the loss Ps of the nanocrystalline core is <100W / Kg.

9. A nanocrystalline iron core, characterized in that: Obtained according to the preparation method according to any one of claims 1 to 8.

10. A pulse transformer, characterized in that: It comprises the nanocrystalline iron core obtained by the preparation method according to any one of claims 1 to 8 or the nanocrystalline iron core according to claim 9.